Knowledge, attitudes and practices of migrant workers and doctors towards migrant health in Singapore - Ang, Jia Wei (2017)
Background: Low-wage non-domestic migrant workers are a large but vulnerable population in Singapore. This study describes potential healthcare barriers and mental health issues faced, and identifies subgroups of workers at higher risk.